2020
DOI: 10.3389/fbioe.2020.00964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Knee Braces in ACL-Deficient Patients

Abstract: Knee braces are often used during rehabilitation after ACL injury. There are two main concepts, rigid and soft braces, but studies comparing the two show conflicting results. Most studies used movement tasks with low translational or rotational loads and did not provide joint kinematics. Therefore, the purpose of this study was to investigate the influence of two different knee braces (rigid vs. soft) on knee joint kinematics in ACL-deficient patients compared to an unbraced control condition using two tasks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…There is a paucity of evidence in the current literature to describe minimal clinically important differences (MCID) values for kinematic and kinematic factors in the reduction of ACL injuries. Focke et al 57 have noted that no previous studies have reported MCID for knee joint kinematics in the coronal and transverse planes during locomotion tasks.…”
Section: Discussionmentioning
confidence: 98%
“…There is a paucity of evidence in the current literature to describe minimal clinically important differences (MCID) values for kinematic and kinematic factors in the reduction of ACL injuries. Focke et al 57 have noted that no previous studies have reported MCID for knee joint kinematics in the coronal and transverse planes during locomotion tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Application of markers on clothing increases the risk of relative movement between the bony segment and the marker ( Milner, 2008 ). The application of other methods such as clusters, often reported for knee brace analyses ( Focke et al, 2020 ; Turner et al, 2021 ), is not applicable for the hip joint as the pelvis was entirely covered by the brace and adjoining segments (thighs and torso) possess large portions of wobbling mass. However, as the pelvis belt of the brace was fitted very tightly, relative movement between the pelvis and the brace is probably small but cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Knee braces have traditionally been used in the post-operative period following ACL reconstruction but considerable debate exists in literature regarding its efficacy and rationale of use. 5,6 Graft site protection, limiting varus-valgus stress and reducing post-operative pain are commonly cited reasons for using it while concern for lost of motion is the most common reason for not using it. 3,4 Our study consisted of 60 patients (Mean age 27.27; SD±4.6), randomized into two groups where half of the patients were given a unhinged long extension knee brace immediately post operatively while the other half were not given any bracing.…”
Section: Discussionmentioning
confidence: 99%
“…Data reported so far is inconclusive regarding the need for knee bracing after ACL reconstruction. 5,6 Purpose of this study is to compare the functional outcome and pain control in patients using knee immobilizer with those not using it in the immediate post-operative period.…”
Section: Introductionmentioning
confidence: 99%